2014
DOI: 10.1016/j.bbalip.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Induction of insulin secretion by apolipoprotein M, a carrier for sphingosine 1-phosphate

Abstract: ApoM augmented insulin secretion by maintaining the S1P concentration under both in vivo and in vitro conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 39 publications
4
58
1
1
Order By: Relevance
“…Although data are limited at present, several papers have proposed that S1P bound to ApoM also possesses physiologic properties different from those of S1P bound to albumin for several physiologic properties other than cell proliferation and fibrosis; S1P bound to ApoM on HDL has a greater effect in maintaining the endothelial barrier (61) and on the secretion of insulin from pancreatic β‐cells (33), whereas S1P carried on ApoM has a suppressive effect on the inflammation of endothelial cells (16) and the induction of PAI‐1 (62), suggesting that the protective properties of S1P against human disorders may be augmented when bound to ApoM, whereas the harmful aspects of S1P in general may be attenuated. Whether S1P possesses beneficial or harmful properties in terms of human diseases has been controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although data are limited at present, several papers have proposed that S1P bound to ApoM also possesses physiologic properties different from those of S1P bound to albumin for several physiologic properties other than cell proliferation and fibrosis; S1P bound to ApoM on HDL has a greater effect in maintaining the endothelial barrier (61) and on the secretion of insulin from pancreatic β‐cells (33), whereas S1P carried on ApoM has a suppressive effect on the inflammation of endothelial cells (16) and the induction of PAI‐1 (62), suggesting that the protective properties of S1P against human disorders may be augmented when bound to ApoM, whereas the harmful aspects of S1P in general may be attenuated. Whether S1P possesses beneficial or harmful properties in terms of human diseases has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2011, when ApoM was first ABBREVIATIONS: ApoM, apolipoprotein M; BW, body weight; Col, collagen; Ctgf, connective tissue growth factor; FBS, fetal bovine serum; Fn, fibronectin; GFP, green fluorescent protein; HIGA, hyper-IgA; KO, knockout; PAS, periodic acid-Schiff; PTX, pertussis toxin; rApoM, recombinant ApoM; S1P, sphingosine 1-phosphate; siApoM, small interfering RNA against murine ApoM; siCtl, control siRNA; WT, wild type established as a carrier of S1P (25), we and others have demonstrated that ApoM is not actually a carrier of S1P, but rather is a modulator of S1P metabolism, and S1P bound to albumin is unstable in plasma, whereas S1P bound to ApoM is stable (30)(31)(32). We were able to modulate the plasma S1P levels continuously using the adenoviral gene transfer of ApoM or the knockdown of ApoM in an in vivo siRNA system (33,34). The epidemiologic association between HDL and the progression of chronic kidney diseases also prompted us to investigate the association between S1P and IgA nephropathy (35,36).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In the plasma, S1P is carried by apolipoprotein M in a complex with high-density lipoprotein (HDL) (Christoffersen et al 2011). Apolipoprotein M not only functions as a vehicle to carry and deliver its S1P to different tissues but to also stimulate S1P synthesis in the liver (Liu et al 2014) and to induce insulin secretion (Kurano et al 2014).…”
Section: Sphingolipid Metabolismmentioning
confidence: 99%
“…More recent studies have extended the potential impact of HDL-S1P to other cells, including pancreatic beta cells, where it was shown to improve insulin secretion, notably under conditions of endoreticulum stress. 41 …”
Section: D F Ementioning
confidence: 99%